The role of the sports and exercise medicine physician in the national health service. Issue 2 (20th January 2011) - O'Halloran, P; Brown, V Tzortziou; Morgan, K; Maffulli, N; Perry, M; Morrissey, D
Abstract : Objectives: To investigate the opinions of general practitioners, orthopaedic surgeons, rheumatologists, sport and exercise medicine (SEM) registrars and public health consultants on training, caseload, the most appropriate setting and the position of SEM within the National Health Service (NHS) in the UK. Method: A cross-sectional questionnaire-based survey investigated the opinions of the above professionals from three primary care trusts and associated hospitals in London and Birmingham. Results: With a 50% response rate (n = 226), 93% (208/224) of participants felt that there was a role for SEM in the NHS. 56% (124/223) agreed that this role should be in both primary and secondary care. 64% (136/212) of participants felt that their practice would benefit from the input of a SEM physician and 95% (191/202) would consider referring patients to SEM services. 74% (165/222) agreed that SEM should have a public health role, and 63% (140/222) believed that these responsibilities should be evenly balanced with the treatment of sports injuries. Despite the emphasis on public health work from SEM policy makers, none of the SEM registrars selected public health as an important training area. 31% (44/140) of participants felt that a lack of education in the medical profession regarding SEM represented the greatest hindrance to its development in the NHS. Conclusion: Several areas of agreement were demonstrated across the specialties, many of which matched the views of policy makers. This study involved participants from a range of cognate disciplines and was the first to investigate this issue since SEM was recognised as a specialty in 2005.